2008
DOI: 10.1007/s11886-008-0077-2
|View full text |Cite
|
Sign up to set email alerts
|

When high is low: Raising low levels of high-density lipoprotein cholesterol

Abstract: Low serum levels of high-density lipoprotein cholesterol (HDL-C) are highly prevalent and are recognized as an independent risk factor for cardiovascular morbidity (myocardial infarction, stroke, peripheral arterial disease, and restenosis after coronary stenting) and mortality. HDL plays an important role in modulating atherogenesis, although its functions are varied and complex and the mechanisms for its antiatherogenic effects have not been completely elucidated. The inverse relationship between HDL-C and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…25,[27][28][29][30][31][32][33][34] Thus, the analyses presented are limited to C-reactive protein (CRP), hemoglobin A1C (hgA1C), and high-density lipoprotein (HDL) cholesterol.…”
Section: Blood Specimen Collection and Assaysmentioning
confidence: 99%
“…25,[27][28][29][30][31][32][33][34] Thus, the analyses presented are limited to C-reactive protein (CRP), hemoglobin A1C (hgA1C), and high-density lipoprotein (HDL) cholesterol.…”
Section: Blood Specimen Collection and Assaysmentioning
confidence: 99%
“…Total cholesterol (TC) is composed of 3 main types of lipoproteins—low-density lipoprotein (LDL), high-density lipoprotein (HDL), and very-low-density lipoprotein (VLDL) [4,5]. The association between elevated LDL cholesterol (LDL-C) and increased risk for cardiovascular events is well established [6], and other lipid parameters are also predictive of cardiovascular risk, including high non-HDL [4], low HDL [7], and elevated triglyceride (TG) levels [8]. …”
Section: Introductionmentioning
confidence: 99%
“…33 HDL particles are widely believed to be atheroprotective because of their capacity to drive reverse cholesterol transport, normalize endothelial dysfunction, and inhibit oxidation, inflammation, insulin resistance, and thrombosis. 34 Hence, the decline in HDL-C with lung transplantation could indicate an increase in cardiovascular risk. Studies in other populations have consistently demonstrated an increased risk for cardiovascular events on the order of 2e3% per 1 mg/dL reduction in HDL-C. 35 While the magnitude of the risk attributable to the lipid changes observed in patients undergoing lung transplantation remains unclear, the median decline in HDL-C of 25 mg/dL is substantial, and cardiovascular mortality remains a major contributor to death following lung transplantation, accounting for nearly 11% of deaths within the first 30 days of transplantation.…”
Section: Discussionmentioning
confidence: 99%